Impairments of spatial learning and memory following intrahippocampal injection in rats of 3-mercaptopropionic acid-modified CdTe quantum dots and molecular mechanisms - Wu T (Dove Medical Press, 2016)
Tianshu Wu,1,2 Keyu He,1,2 Shengjun Ang,1,2 Jiali Ying,1,2 Shihan Zhang,1,2 Ting Zhang,1,2 Yuying Xue,1,2 Meng Tang1,2 1Key Laboratory of Environmental Medicine and Engineering, Ministry of Education, School of Public Health, Collaborative Innovation Center of Suzhou Nano Science and Technology, 2Jiangsu Key Laboratory for Biomaterials and Devices, Southeast University, Nanjing, People’s Republic of China Abstract: With the rapid development of nanotechnology, quantum dots (QDs) as advanced nanotechnology products have been widely used in neuroscience, including basic neurological studies and diagnosis or therapy for neurological disorders, due to their superior optical properties. In recent years, there has been intense concern regarding the toxicity of QDs, with a growing number of studies. However, knowledge of neurotoxic consequences of QDs applied in living organisms is lagging behind their development, even if several studies have attempted to evaluate the toxicity of QDs on neural cells. The aim of this study was to evaluate the adverse effects of intrahippocampal injection in rats of 3-mercaptopropionic acid (MPA)-modified CdTe QDs and underlying mechanisms. First of all, we observed impairments in learning efficiency and spatial memory in the MPA-modified CdTe QD-treated rats by using open-field and Y-maze tests, which could be attributed to pathological changes and disruption of ultrastructure of neurons and synapses in the hippocampus. In order to find the mechanisms causing these effects, transcriptome sequencing (RNA-seq), an advanced technology, was used to gain the potentially molecular targets of MPA-modified CdTe QDs. According to ample data from RNA-seq, we chose the signaling pathways of PI3K–Akt and MPAK–ERK to do a thorough investigation, because they play important roles in synaptic plasticity, long-term potentiation, and spatial memory. The data demonstrated that phosphorylated Akt (p-Akt), p-ERK1/2, and c-FOS signal transductions in the hippocampus of rats were involved in the mechanism underlying spatial learning and memory impairments caused by 3.5 nm MPA-modified CdTe QDs. Keywords: CdTe quantum dots, neurotoxicology, nanotoxicology, learning and memory, RNA-seq, p-AKT, p-ERK1/2, c-FOS